Categorizing the effects of knowledge management practices on SMES: a literature review - Escobar-Castillo, Adalberto (2023)
Large firms have managed to design robust knowledge management (KM) systems that help to create more effective responses to turbulent environments. On contrary, small and medium-sized enterprises (SMEs), which often suffer from the liability of smallness, usually carry out KM practices in a more informal and less planned manner. The objective of this research is to characterize the effects of KM practices in SMEs. The designed documentary review systematically analyzed 276 publications in journals indexed in Scopus in 2022. The main results suggest a tendency to study the dimensions of KM, such as dynamic technological capability, human capital, and their effects on financial and innovative performance, among others. The findings contribute to the literature by reordering information provided by scientific publications and revealing the dependent, mediating, and moderating variables linkedto KM that are currently used by SMEs.